3D Networks of Silver Nanorod–Nanoparticle Hybrids via Aerosol Jetting Printing for Flexible Electrode. Issue 1 (12th August 2022) - Zhao, Danjiao; Wu, Yu; Lin, Aiping; Zhang, Jidi; Lu, Cheng; Bai, Xiaojing; Wang, Shufen; Fan, Lanlan; Cao, Lei; Liu, Sida; Gu, Feng
Abstract : To satisfy the functional requirements for next‐generation electronic and optoelectronic devices, diverse protocols have thus been developed for preparing transparent flexible electrodes (TFEs) of metallic nanowires with high flexibility and conductivity, while flexible electrodes with 3D configuration have become a burgeoning frontier. Herein, an innovative 3D network of silver nanorod–nanoparticle hybrids (Ag NNH) is realized by a facile aerosol jet printing (AJP) technique. A dynamic assembly mechanism based on the AJP of silver nanowires (AgNWs) ink is proposed, suggesting a favorable evaporation‐induced migration and assembly process along with the coalescence of deposited droplets. The initially formed Ag NNH random network optimizes the wettability, spreading, and pinning of the droplets, shaping the consecutive deposition behavior of the aerosol droplets for constructing the 3D Ag NNH networks. Planar micro‐supercapacitor (MSC) devices are developed using the Ag NNH network as flexible microelectrode, and a competitive areal capacitance performance has been demonstrated in comparison with other Ag‐based devices. It is envisioned that the as‐developed approach will provide an optional approach for developing future electronic and optoelectronic devices with fascinating hierarchical features. Abstract : An innovative 3D network of silver nanorod–nanoparticle hybrids (Ag NNH) is realized by a facile aerosol jet printing technique. A dynamic assembly mechanism based on the aerosol jet printing of silver nanowires ink is proposed, suggesting a favorable evaporation‐induced migration and assembly process along with the coalescence of deposited droplets.